2020
DOI: 10.1021/acsmedchemlett.0c00120
|View full text |Cite
|
Sign up to set email alerts
|

Brain Penetrable Inhibitors of Ceramide Galactosyltransferase for the Treatment of Lysosomal Storage Disorders

Abstract: Metachromatic leukodystrophy (MLD) is a rare, genetic lysosomal storage disorder caused by the deficiency of arylsulfatase A enzyme, which results in the accumulation of sulfatide in the lysosomes of the tissues of central and peripheral nervous systems, leading to progressive demyelination and neurodegeneration. Currently there is no cure for this disease, and the only approved therapy, hematopoietic stem cell transplant, has limitations. We proposed substrate reduction therapy (SRT) as a novel approach to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Another potential SRT target for Krabbe disease is ceramide galactosyltransferase (CGT). CGT is the enzyme responsible for the addition of galactose to ceramide and is only one enzymatic step removed from psychosine synthesis [ 40 ]. A new class of brain-penetrable compounds has been described that efficiently inhibit CGT activity [ 40 ].…”
Section: The Evolution and Current Status Of Therapies For Krabbe Diseasementioning
confidence: 99%
“…Another potential SRT target for Krabbe disease is ceramide galactosyltransferase (CGT). CGT is the enzyme responsible for the addition of galactose to ceramide and is only one enzymatic step removed from psychosine synthesis [ 40 ]. A new class of brain-penetrable compounds has been described that efficiently inhibit CGT activity [ 40 ].…”
Section: The Evolution and Current Status Of Therapies For Krabbe Diseasementioning
confidence: 99%
“…The ability to selectively inhibit the synthesis of non-hydroxylated galactosylceramides should be a useful attribute to enable the further understanding of the roles of the different hydroxylated species. Given that CGT inhibitors are actively being pursued as potential SRT therapy for KD and MLD 15 , further studies will be necessary to fully understand how to balance their safety and therapeutic benefit.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of small molecules that inhibit the synthesis of galactosylceramide-based glycolipids that accumulate in KD and MLD is an area of active research 15 . Studies using small molecule glucosylceramide synthase inhibitors to reduce the abundance of the glycolipids that accumulate in Gaucher disease, Fabry disease, GM1 gangliosidosis, and GM2 gangliosidosis, have demonstrated the benefits of substrate reduction therapy 16 – 20 .…”
Section: Introductionmentioning
confidence: 99%
“…The gene UGT8 encodes for ceramide galactosyltransferase (CGT), which catalyzes the final step for galactosylceramide synthesis. Following a search of 30,000 compounds for their ability to inhibit CGT, a thienopyridine was identified and further optimized, resulting in a drug (compound 19) that is an efficacious in vivo inhibitor of CGT that is both orally bioavailable and enters the CNS ( 60 ). In vivo testing in normal mice revealed that this compound was able to inhibit the production of both galactosylceramide and sulfatide in the brain and kidney ( 60 ).…”
Section: Substrate Reduction Therapy Targeting Ceramide Galactosyltransferasementioning
confidence: 99%
“…Following a search of 30,000 compounds for their ability to inhibit CGT, a thienopyridine was identified and further optimized, resulting in a drug (compound 19) that is an efficacious in vivo inhibitor of CGT that is both orally bioavailable and enters the CNS ( 60 ). In vivo testing in normal mice revealed that this compound was able to inhibit the production of both galactosylceramide and sulfatide in the brain and kidney ( 60 ). Additional in vivo studies that examine the therapeutic efficacy in mouse models of Krabbe disease and/or metachromatic leukodystrophy are anticipated.…”
Section: Substrate Reduction Therapy Targeting Ceramide Galactosyltransferasementioning
confidence: 99%